ANALYSIS THE EFFICIENCY OF BOILER 2011 UA WATER TUBE TYPE AT PT PERTAMINA RU III (PERSERO) PLAJU - Dian Dwi Lestari; Isdaryanto Iskandar; Wendi Wendi (Bajang Institute, 2022)
One of the most important tools in steam production in the oil and gas industry is a boiler. Along with the increasing demand for steam, it is necessary to think about ways to increase the efficiency of the boiler. A boiler or steam boiler is a closed vessel-shaped device used to produce steam or steam. Boilers are designed to transfer heat from a combustion source. With Used the direct method (Direct Method) to calculate boiler efficiency. The pressure and temperature data of the feed water and steam is processed through the data interpolation process to obtain the enthalpy value of the feed water and steam enthalpy. Based on the calculation results obtained boiler efficiency results of 78.11%, 78.27%, and 79.75% with an average efficiency of 78.71%, and from the results of boiler efficiency calculations from the report of PT Pertamina RU III (Persero) obtained results of 89,75% in 1991. The efficiency of the above boiler has decreased by 11.04%. The decrease was caused by several factors, namely shells, valves, and instrumentation that had been eaten by age and damaged tubes.